HUBUNGAN ANTARA PERAN DUKUNGAN KELUARGA DENGAN RESIKO DEPRESI PERINATAL DI RUMAH SAKIT MUHAMMADIYAH SURABAYA - Achmada Nadia Shobrina; Era Catur Prasetya; Ninuk Dwi Ariningtyas; Uning Marlina (PROCEEDING UMSURABAYA, 2023)
Perinatal depression is a feeling disorder that occurs during pregnancy or after pregnancy or both that lasts more than 14 days and interferes with the mother's quality of life. Perinatal depression appear as the result of various risk factor, divided into family factor, family financial factor, mother’s health factor and demographics factor. to determine the relationship between the role of family support and the risk of perinatal depression at the Muhammadiyah Hospital in Surabaya. This research was conducted with analytic observational using cross sectional method. Respondents were selected by simple random sampling technique. A total of 96 respondents obstetric polyclinic patients at Muhammadiyah Surabaya Hospital filled out the Edinburgh Postnatal Depression Scale (EPDS) questionnaire and the Apgar Family questionnaire. Data were analyzed using the Spearman correlation test on the SPSS platform. The results of this study were obtained for good family support obtained 80 (83.3%), not good 11(11.5%) and those who get family support are not good 5 (5.2%). For the results of the level of depression, it was found that 38 people (39.6%) had no risk of depression, 30 people (31.3%) had disorders that might cause discomfort and 28 people (29.2%) were at risk of depression. The results of the Spearman bivariate test analysis yielded a value of p = 0.047 (p <0.05) and r = -0.204.The results of this study indicate that there is a relationship between family support and perinatal depression. There is a significant relationship between family support and perinatal depression at Muhammadiyah Surabaya Hospital.Keyword: Family Support, perinatal depression